Smart Street Lighting Enabled by Wireless Sensor Networks: A Path to Energy Efficiency and Fault Monitoring - Aparna M. Bagde; Shubhangi Pasalkar; Nishanti Naidu (International Journal of Wireless Security and Networks, 2025)
The increasing demand for energy efficiency and smart city infrastructure has led to the adoption of innovative technologies such as wireless sensor networks (WSNs) in street lighting systems. This research explores the design and implementation of a smart street lighting system (SSLS) integrated with WSNs to enhance energy efficiency and enable real-time fault detection. The proposed system utilizes a network of wireless sensors to monitor ambient light levels, vehicular movement, and pedestrian activity, dynamically adjusting the brightness of streetlights to optimize energy consumption. In addition, the system incorporates fault detection mechanisms that identify and report issues such as lamp failures, voltage fluctuations, and network disruptions, ensuring minimal maintenance delays and improved operational reliability. By leveraging internet of things (IoT)-enabled WSNs, the SSLS reduces energy wastage, enhances urban safety, and provides a scalable solution for modern cities. Simulation results and prototype testing demonstrate up to 40% energy savings compared to traditional systems, along with a significant improvement in maintenance response times. This study highlights the potential of WSN-based smart lighting solutions in transforming urban lighting systems, contributing to sustainable urban development, and supporting smart city initiatives. Future work focuses on integrating renewable energy sources and advanced artificial intelligence algorithms for predictive maintenance and further optimization.
Keywords: ambient light levels; network disruptions; pedestrian activity; real-time fault detection; vehicular movement; voltage fluctuations; wireless sensor networks